1976
DOI: 10.4992/psycholres1954.18.14
|View full text |Cite
|
Sign up to set email alerts
|

Children's Sorting Behavior as a Function of Conceptual Ability and Frequency of Instances

Abstract: In order to assess S's concept utilization in learning the sorting tasks, preschool children were given either a conceptual sorting task (CST) or a half conceptual sorting task (HST). The results revealed that CST was learned faster than HST by the Ss with high conceptual ability (Exp. I) and in the sorting tasks with high frequency instances (Exp. II), and that both sortings were learned almost at the same rate by the Ss with low ability and in the sorting tasks with low frequency. The superiority of CST over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1978
1978
1980
1980

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…As for the frequency of instances, children's knowledge of conceptual categories was greater for the high-frequency than for the low-frequency pairs. This frequency effect is in line with the previous finding (Sugimura, 1976) that kindergarten children given the high-frequency instances could more easily use concepts in learning the sorting tasks than those given the low-frequency instances. As the instances with high frequency belong more evidently to their categories by definition and are more familiar with children at this age than those with low frequency the subjects can more easily retrieve their category names from the instances.…”
Section: Discussionsupporting
confidence: 91%
“…As for the frequency of instances, children's knowledge of conceptual categories was greater for the high-frequency than for the low-frequency pairs. This frequency effect is in line with the previous finding (Sugimura, 1976) that kindergarten children given the high-frequency instances could more easily use concepts in learning the sorting tasks than those given the low-frequency instances. As the instances with high frequency belong more evidently to their categories by definition and are more familiar with children at this age than those with low frequency the subjects can more easily retrieve their category names from the instances.…”
Section: Discussionsupporting
confidence: 91%
“…These were interpreted to show that children's ability to use concept names in learning the sorting tasks increased with age. Further studies (Sugimura, 1976;Sugimura & Terao, 1976b) showed that the use of concept names by 5-and 6-yr.-old children depended on their conceptual ability and frequencies of instances used in the sorting tasks.…”
mentioning
confidence: 98%